Digital Endocasts From Skulls to Brains (Replacement of Neanderthals by Modern Humans Series,, 2018)
This book is dedicated to a specific component of paleoneurology, probably the most essential one: endocasts. A series of original papers collected here focuses on describing methods and techniques that are dedicated to reconstruct and study fossil endocasts through computed tools. The book is particularly oriented toward hominid paleoneurology, although it also includes chapters on different taxa to provide a more general view of current perspectives and problems in evolutionary neuroanatomy. The first part of the book concerns techniques and tools to cast endocranial anatomy. The second part deals with computed morphometrics, and the third part is devoted to comparative neurobiology. Those who want to approach the field in general terms will find this book especially helpful, as will those researchers working with endocranial anatomy and brain evolution. The book will also be useful for researchers and graduate students in anthropology, bioarchaeology, medicine, and related fields.